Improving mental health, sleep, and decision-making skills through mindfulness practice - Akter, Moslima; Naher, Lutfun; Ahmed, Oli (International Journal of Public Health Science (IJPHS), 2025)
Most of the previous studies on the efficiency of mindfulness to improve mental health states, and sleep quality, have focused on clinical samples. The present study aimed to examine the impact of mindfulness intervention training on mental health (depression, anxiety), sleep quality, life satisfaction, and decision-making skills in non-clinical sample. Using a non equivalent comparison group design, 52 university students were recruited via convenience sampling technique and randomly distributed into two groups – treatment and comparison groups. The treatment group a 30-hour of mindfulness training over one month. Results showed that mindfulness training significantly reduced depressive symptoms and improved sleep quality and life satisfaction in treatment group, although changes in anxiety and decision-making skills were non-significant. These findings contribute to the mindfulness literature and emphasize the importance of mindfulness practice in enhancing mental health and well-being in non-clinical settings.